An analysis of Religion-Political relations in Terms of Social Contract Theory - Mehmet fatih Deniz; Mehmet fatih Deniz (Turkish Academic Research Review)

(untitled)
This work analyzes how thereligious-political relationships function inSocial Contract Theory.During the 17th and 18th centuries, the terminology of Social Contract wasdeveloped by many thinkers of the age such as Thomas Hobbs, John Locke, andJean-Jacques Rousseau to counterthe classic empery arguments of both thearistocratic monarchy and of the church. The principal aim of this study is toinvestigate and analyze how this theoretic positionhas linked itself tomodern-day political philosophyon religious and political relations.